2013
DOI: 10.1016/j.hrthm.2012.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of the cardiac sodium channel, connexin43, and plakoglobin at the intercalated disk in patients with arrhythmogenic cardiomyopathy

Abstract: Background Arrhythmogenic cardiomyopathy (AC) is tightly associated with desmosomal mutations in the majority of patients. Arrhythmogenesis in AC patients is likely related to remodeling of cardiac gap junctions and increased levels of fibrosis. Recently, using experimental models, we also identified sodium channel dysfunction secondary to desmosomal dysfunction. The aim of the present study was to assess the immunoreactive signal levels of the sodium channel protein NaV1.5, as well as Connexin43 and Plakoglob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
122
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(127 citation statements)
references
References 33 publications
2
122
0
Order By: Relevance
“…Moreover, a reduction of the immunoreactive signal of sodium channel Na v 1.5 protein in myocardium, which might contribute to arrhythmia vulnerability, has also been reported in ARVC, in addition to the changes in plakoglobin and connexin 43. 7) Further study is needed to elucidate precisely how severe arrhythmia develops in patients with ARVC. Study limitations: The genes encoding intercellular junction proteins in the present patients with ARVC were not analyzed, although patients with myocarditis were excluded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a reduction of the immunoreactive signal of sodium channel Na v 1.5 protein in myocardium, which might contribute to arrhythmia vulnerability, has also been reported in ARVC, in addition to the changes in plakoglobin and connexin 43. 7) Further study is needed to elucidate precisely how severe arrhythmia develops in patients with ARVC. Study limitations: The genes encoding intercellular junction proteins in the present patients with ARVC were not analyzed, although patients with myocarditis were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…6) Moreover, the previous study showed that immunoreactive signals for connexin 43, a gap junction component, as well as plakoglobin, were also disturbed in around 70% of patients with ARVC. 7) However, no report has examined the relationships between these protein expressions and the clinical characteristics in ARVC.…”
mentioning
confidence: 99%
“…These findings led to hypothesize that life-threatening ventricular arrhythmias could occur in AC patients, even preceding the structural abnormalities (pre-phenotypic stage) due to electrical uncoupling and reduced sodium current. However, this hypothesis remains to be proven in human AC patients, where only a reduced immunoreactive signal at intercalated disc for the major protein subunit of the sodium channel Nav1.5 has been demonstrated [103].…”
Section: Gap Junction and Ion Channel Remodellingmentioning
confidence: 97%
“…Diminished expression of connexin-43 at intercellular junction was demonstrated in most of AC cases, suggesting that impaired mechanical coupling might also account for abnormal electrical coupling through gap-junction remodelling. Moreover, cardiac sodium current was found to be reduced in experimental models of AC [28,29,[102][103][104]. These findings led to hypothesize that life-threatening ventricular arrhythmias could occur in AC patients, even preceding the structural abnormalities (pre-phenotypic stage) due to electrical uncoupling and reduced sodium current.…”
Section: Gap Junction and Ion Channel Remodellingmentioning
confidence: 98%
“…A further aspect of this fascinating story of interaction between closely apposed protein complexes of the ID, exerting entirely different functions, relates to arrhythmogenic cardiomyopathy. This disease is primarily due to mutations in desmosomal proteins, (Campuzano et al, 2013) but leads to change in expression and/ or malfunction of the partner protein complexes in the ID (Asimaki et al, 2009;Noorman et al, 2013). This is a further interesting example showing that the analysis of a disease mechanism can amend to new knowledge about basic cellular function.…”
Section: Introduction: Engineering Cardiac Tissuementioning
confidence: 99%